Contemporary maritime piracy international law, strategy, and diplomacy at sea - Kraska, James (Contemporary military, strategic, and security issues, 2011)
"This volume provides a concise introduction to the issues and debates regarding modern piracy that include naval operations, law, and diplomacy, and focuses on the recent surge of attacks off the coast of Africa and Asia"--